MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA SD NEGERI 098166 DI PERUMNAS BATU ONOM UNTUK MATA PELAJARAN MATEMATIKA MELALUI METODE ROLE PLAYING - Simanjuntak, Melvin; Rianti Lumbantobing; Cintia Malau; Juli Tamara Sinaga; Ratu Simanjuntak; Haway Sinaga; Morinda Harianja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics education plays a very important role in shaping attitudes, concepts and mindsets to improve critical thinking skills in learning. Therefore, mathematics learning is very necessary from elementary school (SD) so that students can have mastery where in each mathematics subject students can have the ability to solve and understand the concepts in the questions given. This study aims to identify and analyze the effectiveness of the role playing method in improving elementary school (SD) students' learning motivation in mathematics. The role playing method, which allows students to play an active role in learning scenarios, is expected to make mathematical concepts more concrete and relevant to their daily lives. This study was conducted using a qualitative descriptive approach through literature analysis and observation of the application of role playing in the classroom. The results of the study showed an increase in learning motivation and understanding of mathematics material after the application of role playing. Students who were previously less motivated showed increased enthusiasm and active participation in learning. This article also provides guidance on how to design and implement role playing in mathematics learning in elementary school. Keywords: Keywords: learning motivation, role playing, mathematics learning, elementary school.